The role of a community health service in the prevention of violence against women. Issue 4 (1st December 2015) - Upston, Bronwyn; Poljski, Carolyn; Wirtz, Helen
Abstract : Link Health and Community (previously known as MonashLink Community Health Service) in Melbourne, Australia, has adopted an innovative approach to its role in the prevention of violence against women. By building on its local and regional partnerships and long-standing work in tertiary prevention, over the past 6 years Link Health and Community has strategically increased its capacity for secondary and primary prevention, resulting in a whole-of-organization approach to the prevention of violence against women. The adoption of a socioecological framework that recognizes that violence against women is caused by the complex interplay of many factors across multiple levels of influence has informed the community health service's multiple roles in the prevention of violence against women. We describe the roles community health services can play in the prevention of violence against women – as a partner and setting for prevention programs, in planning and service provision.